Complete Remission Obtained with Azacitidine in a Patient with Concomitant Therapy Related Myeloid Neoplasm and Pulmonary Mucormycosis - Saveria Capria; Federico De Angelis; Giuseppe Gentile; Silvia Maria Trisolini; Simonetta Brocchieri; Martina Canichella; Patrizia Chiusolo; Alessandra Micozzi; Robin Foà; Giovanna Meloni (Mediterranean Journal of Hematology and Infectious Diseases)
Mucormycosis is the third cause of invasive mycosis after candidiasis and aspergillosis in AML patients, representing a poor prognostic factor associated with a high rate of fatal outcome.